2010
DOI: 10.1007/s00198-010-1199-0
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of interventions by healthcare professionals on community-dwelling postmenopausal women with osteoporosis

Abstract: From this review, it was found that some outcome measures of such non-drug interventions still required further studies. Future studies should use validated instruments to assess the outcomes, with focus on common definitions of interventions and outcome measures, more intensive one-to-one interventions, appropriate control groups, adequate randomization procedures, and also provide information on effect size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…We also note that none of the studies examined the impact of the pharmacist interventions on osteoporosis treatment adherence or considered pharmacists’ experience or satisfaction with the osteoporosis management programs. Recent reviews of the literature identify that strategies that enhance patient and healthcare provider communication and treatment follow-up may be key to improving adherence to osteoporosis pharmacotherapy [5, 47, 48]. Further study is thus important to identify the impact of pharmacy interventions on treatment initiation and adherence to therapy, as well as to examine the feasibility of osteoporosis management in community pharmacy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also note that none of the studies examined the impact of the pharmacist interventions on osteoporosis treatment adherence or considered pharmacists’ experience or satisfaction with the osteoporosis management programs. Recent reviews of the literature identify that strategies that enhance patient and healthcare provider communication and treatment follow-up may be key to improving adherence to osteoporosis pharmacotherapy [5, 47, 48]. Further study is thus important to identify the impact of pharmacy interventions on treatment initiation and adherence to therapy, as well as to examine the feasibility of osteoporosis management in community pharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…Further study is thus important to identify the impact of pharmacy interventions on treatment initiation and adherence to therapy, as well as to examine the feasibility of osteoporosis management in community pharmacy. Interventions in osteoporosis management by physicians, physiotherapists, nurses, dieticians, and other healthcare professionals working in teams have helped to improve treatment adherence and calcium intake among community-dwelling women [5] and increase BMD testing and osteoporosis treatment rates in patients post-fracture [4]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthcare professionals should receive adequate osteoporosis education in their academic programs in order to give them adequate knowledge of the disease to prepare them for treating this population. A systematic review of interventions by healthcare professionals on community-dwelling postmenopausal women with osteoporosis defined these interventions by consultation with physicians, nurses, pharmacists, physical therapists, and dietitians [8]. Physicians who treat individuals with osteoporosis have additional training after medical school with residencies and possible fellowships to prepare them to treat patients with the disease; therefore, this study investigated osteoporosis knowledge in students who were soon to be nurses, pharmacists, physical therapists, and dietitians.…”
Section: Introductionmentioning
confidence: 99%
“…Second, pharmacists can provide counseling and educate patients on medication use, fall prevention, and the importance of calcium, vitamin D, exercise, and adherence to therapy. A recent review identified that non-drug interventions by healthcare professionals improved quality of life, treatment adherence, and calcium intake among community-dwelling postmenopausal women with osteoporosis 7 . Hence, this study aims to establish the relationship between the bone health and AED use the impact of pharmacist's intervention as well in improving the bone health, particularly in women epileptic patients taking AEDs.…”
Section: Introductionmentioning
confidence: 99%